The Association between Sleep Duration, Breakfast Routine and Nutritional Status in Indonesian Adolescents during COVID-19 Pandemic - Muhammad Nadzir Mushoffa Suja’I; Reny Noviasty; Eva R Kurniawati; Ratih Wirapuspita Wisnuwardani (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2022)
Background: Adolescents are susceptible to nutritional status issues, both undernutrition, and over-nutrition, becoming a public health concern promptly. There were 912 junior and high-school adolescents who were obese and 249 high-school adolescents who had low body mass index (BMI) in Samarinda City. During the COVID-19 pandemic, adolescents experienced changes in sleep duration, and many adolescents were skipping breakfast. Sleep duration and breakfast can affect the nutritional condition of adolescents. Objectives: The purpose of this study was to determine the association between sleep duration, breakfast routine and BMI in Samarinda, Indonesian adolescents during COVID-19 pandemic.Materials and Methods: A total of 340 adolescents was sampled and assessed using a cross-sectional technique to ascertain their sleep duration, breakfast routine, and nutritional status. Nutritional status was classified based on BMI-for-age and z-value BMI. The amount of sleep duration was calculated by the average wake time and sleep time. Breakfast routine was obtained from seven days of breakfast before 9 am. Then, using multivariate analyses were tested for sleep duration, BMI z-value, breakfast routine, and nutritional status.Results: This study revealed that 68.5% had good nutrition, with an average sleep duration of 8 hours (65.9%) and irregular breakfast (59.1%). Nutritional status was significantly influenced by breakfast routine (p=0.044), gender (p<0.001), and mother’s employment (p<0.001). A cubic association was found between sleep duration and BMI (p=0.045); and a significant association between breakfast routines and BMI, independent from age, gender, ethnicity, school.Conclusion: Adolescents must consider their sleep duration and the frequency and composition of their breakfast. Future study in the longitudinal study is needed to explore in more detail.